IMPLEMENTASI PENGGUNAAN APLIKASI ANDROID SEBAGAI SELF-ASSESSMENT DAN MEDIA INFORMASI COVID-19 DI PUSKESMAS DADOK DAN KELURAHAN KAMPUNG LAPAI NANGGALO KOTA PADANG - Augia, Trisfa; Ramadani, Mery; Dahlan, Hendery; Tani, Rizki Ridhatul; Fauziah, Fauziah (LPPM Universitas Andalas, 2020)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. Indonesia reported its first case of COVID-19 on March 2, 2020 and the number continues to grow until now. Until October, 15 2020 the Ministry of Health reported 349,160 confirmed cases of COVID-19 with 12,268 deaths. The COVID-19 Self-Assessment application can help screening of individual and health workers to accelerate case finding and make it easier for health workers to provide curative efforts. Socialization of the COVID-19 Self-Assessment Application in coordination with the Public Health Center Dadok Tunggul Hitam and Kelurahan Kampung Lapai. Activities included introduction, installation, implementation, and monitoring and evaluation of application usage. Participants installed the application on an Android device and implemented the application enthusiastically. It is hoped that this application can make it easier for community to access information related to COVID-19 and carry out screening independently.